The Application of Argumentation Theory to Translation Quality Assessment - Williams, Malcolm (Meta, 2001)
AbstractTranslation quality assessment (TQA) models may be divided into two main types: (1) models with a quantitative dimension, such as SEPT (1979) and Sical (1986), and (2) non-quantitative, textological models, such as Nord (1991) and House (1997). Because it tends to focus on microtextual (sampling, subsentence) analysis and error counts, Type 1 suffers from some major shortcomings. First, because of time constraints, it cannot assess, except on the basis of statistical probabilities, the acceptability of the content of the translation as a whole. Second, the microtextual analysis inevitably hinders any serious assessment of the content macrostructure of the translation. Third, the establishment of an acceptability threshold based on a specific number of errors is vulnerable to criticism both theoretically and in the marketplace. Type 2 cannot offer a cogent acceptability threshold either, precisely because it does not propose error weighting and quantification for individual texts. What is needed is an approach that combines the quantitative and textological dimensions, along the lines proposed by Bensoussan and Rosenhouse (1990) and Larose (1987, 1998). This article outlines a project aimed at making further progress in this direction through the application of argumentation theory to instrumental translations.